STUDY OF STRUCTURAL AND MECHANICAL PROPERTIES OF MIXED FABRICS FOR SPECIAL CLOTHING TYPE «RIPSTOP» - PELYK, Lesia; OSTAPCHUK, Olga; PELEH, Yulia (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The article examines the indicators of the structural and mechanical properties of fabrics for special clothing of the "Ripstop" type with a mixed fiber composition. Their influence on the wear resistance of workwear was analyzed. The fiber composition of mixed fabrics for sewing military clothing includes polyester fibers and cotton fibers. At the same time, cotton fibers provide hygienic properties, and the synthetic component provides good wear and weather resistance. Mixed fabrics are easy to care for and practically do not wrinkle. The fiber composition of the textile material "Greta" of Ukrainian production includes 53% cotton fiber and 47% polyester fiber. A distinctive feature is the special interweaving of fibers, due to which the cotton fibers are on the wrong side, which improves hygienic properties. Due to the polyester fibers, the fabric is durable, resistant to pollution, and is the least prone to change in linear dimensions. It was established that the tearing characteristics of the fabric depend on the type of fibrous composition, the strength of the threads, the structure of the fabric and the methods of its processing. It was found that when stretched in the direction of the warp or weft, the strength of fabrics depends on the strength and number of longitudinal threads in the structure of the fabric, which directly accept the load. It has been studied that as the density and filling of the fabric increases, the mutual connection of its elements, that is, fibers and threads, increases, which leads to an increase in the strength of the textile material. It was established that with an increase in the thickness of the threads and the surface density of the fabric, the strength of the fabric increases. In a textile material, the threads, having mutual interweaving, are bound by friction into a single system. The use of weaves with short overlaps also contributes to the growth of fabric strength, therefore, all things being equal, the reinforced canvas weave provides fabrics with high strength. Conducted studies have shown that elongation indicators during tearing are related, first of all, to the elongation of textile fibers, which is most fully manifested in the structure of the fabric, with the twisting of yarn or threads, with interweaving.